Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan Melalui Kebijakan Deviden pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Busra Efek Indonesia - Satriani, Satriani; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Chalid, Lukman (STIM-LPI Makassar, 2024)
Research objectives: (1) analyze the effect of profitability on dividend policy (2) the effect of leverage on dividend policy (3) the effect of profitability on company value (4) the effect of leverage on company value (5) the effect of dividend policy on value (6) the effect of profitability on company value through dividend policy (7) the influence of leverage on company value through dividend policy in food and beverage sector companies listed on the Indonesian stock exchange.This research uses a data analysis method, namely path analysis, with the research object being food and beverage sector companies listed on the Indonesian Stock Exchange (BEI) in 2020-2022 and using SmartPLS data processing software. The research design used is quantitative, The research results show that: (1) Profitability has a positive and significant effect on dividend policy (2) Leverage has a positive and insignificant effect on dividend policy (3) Profitability has a positive and insignificant effect on company value (4) Leverage has a negative and insignificant effect on company value (5) Dividend policy has a negative and significant effect on company value (6) Profitability has a positive and significant effect on company value through dividend policy (7) Leverage has a negative and insignificant effect on company value through dividend policy in food and beverage sector companies listed on the Indonesian stock exchange in 2020-2022.